Avaliação da atividade antioxidante, fotoprotetora e antiglicante dos extratos das folhas e flores de Moringa oleifera - Gimenis, Janine Mailho [UNESP] (2015)
The development of new drugs with antioxidant action has been an important subject of study, since the current drug therapy for the treatment of diseases such as Alzheimer's, Parkinson's, multiple sclerosis, Huntington's disease, epilepsy and some types of cancer can be performed because the antioxidant properties of many natural and / or synthetic compounds. Thus, the search for new antioxidants is extremely necessary and is currently the subject of interest in new research by the cosmetic, pharmaceutical and nutritional industry. In this context, this work will enable increased knowledge on Moringa oleifera by evaluating the antioxidant potential, sunscreen and anti-glycation of the extracts of this species, besides elucidating ethnobotanical reports of its use and enrich the scientific knowledge of this widely used species with medicinal plant. In addition they are reduced scientific information on the activities to be evaluated in this project